Aquatic plants: Test species sensitivity and minimum data requirement evaluations for chemical risk assessments and aquatic life criteria development for the USA. (July 2018) - Lewis, Michael; Thursby, Glen
Abstract: Phytotoxicity results from the publicly-available ECOTOX database were summarized for 20 chemicals and 188 aquatic plants to determine species sensitivities and the ability of a species-limited toxicity data set to serve as a surrogate for a larger data set. The lowest effect concentrations reducing the sublethal response parameter of interest by 50% relative to the controls (EC50 ) usually varied several orders of magnitude for the 119 freshwater and 69 saltwater plants exposed to the same test chemicals. Generally, algae were more sensitive than floating and benthic species but inter-specific differences for EC50 values were sometimes considerable within and between phyla and no consistently sensitive species was identified for the morphologically-diverse taxa. Consistent equivalencies of the phytotoxicity databases for freshwater-saltwater plants and floating-benthic macrophyte species were not demonstrated. Two species-sensitivity distribution plots (SSDs) were constructed for each of the 20 chemicals, one based on all available phytotoxicity information (range = 10–76 test species) and another based on information for only five species recommended for pesticide hazard evaluations. HC5 values (hazardous concentration to 5% of test species) estimated from the two SSDs usually differed four-fold or less for the same chemical. HC5 values for the five species were often conservative estimates of HC5 values for the more species-populated data sets. Consequently, the collective response of the five test species shows promise as an interim aquatic plant minimum data requirement for aquatic life criteria development. In contrast, the lowest EC50 values for the five species usually were greater than HC5 values for the same test chemicals, a finding important to criteria-supporting Final Plant Values. The conclusions may differ for comparisons based on other test chemicals, test species, response parameters and calculations. Graphical abstract: Image 1 Highlights: Toxic effect concentrations for 188 aquatic plants and 20 chemicals were reviewed. EC50 values within and between phyla varied in an unpredictable manner. No consistently sensitive species was identified across chemicals. HC5 values from SSDs based on small and large data sets varied slightly. The collective response of five species shows promise as a MDR for criteria development.